Any day now toward a Black aesthetic - Neal, Larry 1937-1981 (David Zwirner Books, 2024)
Larry Neal, a poet, dramatist, and critic, was a founding figure of the Black Arts Movement in the 1960s and 1970s in New York. Writing as the arts editor for Liberator magazine, a radical journal published in Harlem, Neal called for Black artists to produce work that was politically oriented, rooted in the Black experience, and written for the Black community. Engaging with fiction, music, drama, and poetry in his texts, he challenged the dominance of the Western art-historical canon and charged Black artists and writers with reshaping artistic traditions according to their own history. As he proclaimed in his essay "The Black Writer's Role," written in 1966, "Black writers must listen to the world with their whole selves--their entire bodies. Must make literature move people. Must want to make our people feel, the way our music makes them feel." The writer Allie Biswas, who selected the texts Neal wrote from 1964 to 1978 included here, introduces the volume, illuminating the rich and varied context in which he produced his work
Keywords: Geschichte 1964-1978; Black arts movement; Philosophie; Ästhetik; Literatur; Neal, Larry / 1937-1981; Neal, Larry - 1937-1981; Aesthetics, Black; African American aesthetics; Arts, Black / Philosophy; Esthétique noire; Esthétique noire américaine; Arts noirs - Philosophie; Arts, Black; Aufsatzsammlung